Ghana Agriculture Production Survey (GAPS): Report on data quality and findings on key indicators 2011/2012 minor season survey - Osei-Akoto, Isaac; Appiah-Kubi, Wilson; Horlu, Godwin; Bonsu, Adwinmea (International Food Policy Research Institute, 2014)
The Ghana Agriculture Production Survey (GAPS) undertaken by the Statistics, Research and Information Directorate (SRID) of the Ministry of Food and Agriculture is designed to provide data on community amenities, characteristics of farm families, utilization of land, use of inputs, outputs of major agricultural commodities, post-farm activities, household incomes, health of farm families, and health of farm animals on an annual basis.